Redox-Responsive Nanocarrier for Controlled Release of Drugs in Inflammatory Skin Diseases - Keerthana Rajes; Karolina A. Walker; Sabrina Hadam; Fatemeh Zabihi; Fiorenza Rancan; Annika Vogt; Rainer Haag (MDPI AG, 2020)
A synthetic route for redox-sensitive and non-sensitive core multi-shell (CMS) carriers with sizes below 20 nm and narrow molecular weight distributions was established. Cyclic voltammetric measurements were conducted characterizing the redox potentials of reduction-sensitive CMS while showcasing its reducibility through glutathione and tris(2-carboxyethyl)-phosphine as a proof of concept. Measurements of reduction-initiated release of the model dye Nile red by time-dependent fluorescence spectroscopy showed a pronounced release for the redox-sensitive CMS nanocarrier (up to 90% within 24 h) while the non-sensitive nanocarriers showed no release in PBS. Penetration experiments using ex vivo human skin showed that the redox-sensitive CMS nanocarrier could deliver higher percentages of the loaded macrocyclic dye meso-tetra (m-hydroxyphenyl) porphyrin (mTHPP) to the skin as compared to the non-sensitive CMS nanocarrier. Encapsulation experiments showed that these CMS nanocarriers can encapsulate dyes or drugs with different molecular weights and hydrophobicity. A drug content of 1 to 6 wt% was achieved for the anti-inflammatory drugs dexamethasone and rapamycin as well as fluorescent dyes such as Nile red and porphyrins. These results show that redox-initiated drug release is a promising strategy to improve the topical drug delivery of macrolide drugs.